PERSON-ORGANIZATION FIT DAN EMPLOYEE ENGAGEMENT: PERAN MODERASI EFFORT REWARD IMBALANCE - Ade Purnamasari; Alice Salendu (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2018)
The present study is aimed at examining the moderating role of effort-reward imbalance (ERI) in the relationship between person-organization fit (PO-Fit) and employee engagement (n = 115). Specifically, this study proposed that a higher ratio in ERI leads the employee to decrease their engagement even when they feel compatible with the organization. Sampling was done through accidental method to employee minimum having high school degree and at least work 1 year in the same organization. A quantitative method was employed and data was collected through an online survey. The study used the ERI Scale constructed by Siegrist, P-O fit Scale constructed by Lee and Wu. Meanwhile, employee engagement scale was develop based on Shuck et al. theories. Testing for moderation effects is done by using Process v2.16.3 tools from Andrew F. Hayes model 1. The results show that ERI negatively moderates the relationship, such that the relationship between person-organization fit and employee engagement is decreasing when employee feel imbalance with the effort they give and reward they receive.